Effect of Sapodilla (Manilkara zapota L.) Leaves Extract on the Lipid Levels of Diabetic Mice Induced with Alloxan - Cinta Atsa Mahesa Rani; Tridiganita Intan Solikhah; Boedi Setiawan (The Indian Veterinary Journal, 2025)
Sapodilla leaves extract has hypocholesterolemic and high antioxidant activity with potential to protect the body from ROS effect. This study used 25 male mice which were divided into 5 groups. The groups consisted of diabetic mice control, diabetic mice treated with pioglitazone 20mg/kg, normal mice control, diabetic mice treated with sapodilla leaves extract at 70mg/kg and 140mg/kg. The results of the study showed that 14 days administration of sapodilla leaves extract at 70 mg/kg and 140 mg/kg decreased the TG, LDL, and TC, while at 140 mg/kg, sapodilla leaf extract increased the HDL level.